Favorable outcome of high-dose chemotherapy and autologous hematopoietic stem cell transplantation in patients with nonmetastatic osteosarcoma and low-degree necrosis - Hong, Kyung Taek; Park, Hyun Jin; Kim, Bo Kyung; An, Hong Yul; Choi, Jung Yoon; Cheon, Jung-Eun; Park, Sung-Hye; Kim, Han-Soo; Kang, Hyoung Jin (Frontiers in Oncology, 2022)
Background: A low-degree tumor necrosis after neoadjuvant chemotherapy is a poor prognostic factor for osteosarcoma (OSA). However, the role of high-dose chemotherapy (HDC) and autologous hematopoietic stem cell transplantation in OSA remains controversial. We analyzed the treatment outcomes and prognostic factors of nonmetastatic OSA and compared the HDC and conventional chemotherapy (CC) outcomes of patients with <90% necrosis after neoadjuvant chemotherapy. Methods: We retrospectively evaluated patients with OSA treated at the Seoul National University Children’s Hospital from 2000 to 2020. Totally, 113 patients with non-metastatic OSA at diagnosis were included. The majority were treated with cisplatin, doxorubicin, and methotrexate as neoadjuvant chemotherapy. This was continued when the postoperative necrosis rate was >90% (good response [GR]), whereas most cases with <90% (poor response [PR]) were changed to chemotherapy. The HDC regimen was composed of melphalan, etoposide, and carboplatin. Results: The median age at diagnosis was 12.6 years (range, 5.0–20.3), and 61.9% of patients were men. The 5-year event-free survival (EFS) and overall survival (OS) rates were 75.8% and 91.5%, respectively. Among these, 59 and 44 patients were included in the GR and PR groups, respectively. The GR group had a better 5-year EFS rate than the PR group (82.4% vs. 67.3%, p=0.071). Age at diagnosis, sex, tumor site, type of neoadjuvant chemotherapy, and degree of tumor necrosis were not different between the PR-HDC (n=24) and PR-CC (n=20) groups. The 5-year EFS and OS rates in the PR-HDC (n=24) and PR-CC (n=20) groups were 78.6% and 53.6% (p=0.065) and 100% and 76.9% (p=0.024), respectively. In the Cox regression analysis, the PR-CC group (hazard ratio, 4.95; p=0.004) and age ≥12 years (hazard ratio, 2.68; p=0.024) were significant risk factors for 5-year EFS. Conclusions: HDC showed favorable outcomes in patients with non-metastatic OSA and <90% necrosis after neoadjuvant chemotherapy.